8(m-1)-7(m+3)=-29

Simple and best practice solution for 8(m-1)-7(m+3)=-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(m-1)-7(m+3)=-29 equation:


Simplifying
8(m + -1) + -7(m + 3) = -29

Reorder the terms:
8(-1 + m) + -7(m + 3) = -29
(-1 * 8 + m * 8) + -7(m + 3) = -29
(-8 + 8m) + -7(m + 3) = -29

Reorder the terms:
-8 + 8m + -7(3 + m) = -29
-8 + 8m + (3 * -7 + m * -7) = -29
-8 + 8m + (-21 + -7m) = -29

Reorder the terms:
-8 + -21 + 8m + -7m = -29

Combine like terms: -8 + -21 = -29
-29 + 8m + -7m = -29

Combine like terms: 8m + -7m = 1m
-29 + 1m = -29

Add '29' to each side of the equation.
-29 + 29 + 1m = -29 + 29

Combine like terms: -29 + 29 = 0
0 + 1m = -29 + 29
1m = -29 + 29

Combine like terms: -29 + 29 = 0
1m = 0

Solving
1m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '1'.
m = 0

Simplifying
m = 0

See similar equations:

| 3x+108=9x-12 | | -5x-3(-x+1)=7 | | N+6=-44 | | 107-7x=29x+23 | | 2x/4=6*3 | | 150-5x=22x+18 | | -6x-6(-4x-11)=12 | | 12x^2-40=17x | | (x-7)=(x+3) | | y=-4(-2)-5 | | 23=m-9 | | 7.31=d+3.31 | | 5x+2x=55 | | 2-7x=1-6x | | x^2-15*8= | | x^3-10x^3+21x=0 | | 12x+11=119 | | y=-2-2-3-2-4 | | (6*2-4)/2 | | x-9y=-21 | | 8+3x/5=x | | x^2-11x+30x=0 | | (15*2x)(8*2x)-15*8= | | 3/10(24/130) | | 55-21=m | | 3x^2-21x=-6x^2-5x-7 | | 3/1024/130= | | 1/3+2/5=11/x | | 3y^2+2y=8 | | 14p^2-23p+8=0 | | -121=7-4p^5/4 | | 2r=14 |

Equations solver categories